Spermiogenesis and ultrastructure of the spermatozoon of the trypanorhynch cestode Aporhynchus menezesi (Aporhynchidae), a parasite of the velvet belly lanternshark Etmopterus spinax (Elasmobranchii: Etmopteridae) - Marigo, Adji Mama; Swiderski, Zdzisław; Bâ, Cheikh Tidiane; Miquel, Jordi (Folia parasitologica, 2011)
Spermiogenesis and the ultrastructural organisation of the spermatozoon of the trypanorhynch cestode Aporhynchus menezesi Noever, Caira, Kuchta et Desjardins, 2010 are described by means of transmission electron microscopy. Type I spermiogenesis of A. menezesi starts with the formation of a differentiation zone containing two centrioles separated by an intercentriolar body constituted by five electron-dense plates. Each centriole gives rise to a free flagellum, which grows at an angle of 90 degrees in relation to a median cytoplasmic process. The nucleus and cortical microtubules elongate along the spermatid body. Later, both flagella rotate and fuse with the median cytoplasmic process. At the final stage of spermiogenesis, the young spermatozoon is detached from the residual cytoplasm by a narrowing of the ring of arched membranes. The mature spermatozoon is a long and filiform cell, tapered at both ends, lacking mitochondria. It is characterized by the presence of two axonemes of the 9+'1' trepaxonematan pattern, the absence of crested bodies, the presence of parallel cortical microtubules and nucleus. This pattern corresponds to the type I spermatozoon of the eucestodes. The anterior extremity of the spermatozoon is characterized by the presence of an arc-like row of up to seven parallel cortical microtubules that partially surrounds the first axoneme. These anterior cortical microtubules are thicker than the posterior microtubules and, consequently, the sperm cell of A. menezesi exhibits two types of cortical microtubules. Another interesting aspect is the presence of alpha-glycogen rosettes. This spermatological pattern is similar to that observed in the spathebothriidean and diphyllobothriidean cestodes.
Keywords: Cestoda; Male; Fish Diseases; cestodózy; Cell Nucleus; spermatogeneze; Flagella; Spermatozoa; Spermatogenesis; mužské pohlaví; buněčné jádro; flagella; žraloci; Microtubules; Animals; Microscopy, Electron, Transmission; zvířata; mikrotubuly; nemoci ryb; spermie; Sharks; Cestode Infections; transmisní elektronová mikroskopie